(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
Decrease in cargo water transportation forces the companies to look for ways on decrease in expenses and increase in business profitability. This article considers the principles of increase in competitiveness of the company of the water transport field due to introduction of systems of the environmental management built on the basis of the register of the ecological aspects of the company.